A remarkable new species of Eutrichopoda Townsend, 1908 (Diptera: Tachinidae: Phasiinae) - Dios, Rodrigo De Vilhena Perez; Nihei, Silvio Shigueo (Zootaxa, 2016)
A new Tachinidae species, Eutrichopoda flavipenna sp. nov. (Diptera: Tachinidae: Phasiinae), from Brazil and Paraguay is described and illustrated by photographs and line drawings. The remarkable yellow, feather-like setae on the hind tibia distinguishes the new species from all other species in the tribe Trichopodini.